Alignment of Epidemiology Practice and Academic Competencies through Effective Collaboration - Glenn, Kimberly R.; Masters, Paula R.; Quinn, Megan A. (Frontiers in Public Health, 2016)
Background: Online learning has recently garnered increased attention as technology use in the classroom grows. However, most of the published approaches regarding this topic in postgraduate education centers on clinical environments. Models of partnerships between applied public health agencies and academic centers to produce mutually beneficial online learning opportunities for graduate-level public health courses have not been explored in the literature. Methods: East Tennessee State University (ETSU) and the Tennessee Department of Health (TDH) partnered to build three online, asynchronous epidemiology modules for an interdisciplinary audience of graduate students. The goal of the modules were to 1) introduce students to a public health issue, 2) provide students with hands-on learning about data and information available through TDH, and 3) allow students to connect theory to practice by having them create a product for use by TDH. TDH created topic-specific modules that would be used within the infectious disease, chronic disease and cancer epidemiology courses and piloted during the 2015-2016 academic term. Results: Conference calls between the two institutions occurred in the spring and the summer of 2015. Two of the three epidemiology modules were presented to ETSU staff for critique and edits at an in-person meeting during the summer. The methods of delivery for each section within a module varied from recorded webinar format to self-guided instruction. One module utilized available learning tools provided by the Centers of Disease Control and Prevention while the other module was constructed entirely using TDH data. Both modules included various exercises and assignments to be conducted in-class and as homework, and concluded with the student being asked to construct a learning product as a final project. The ETSU-TDH team decided that this learning product would be provided back to TDH for possible future use. Discussion: The innovative partnership between a state government agency and an academic institution has demonstrated the need for such collaborations in public health. Understanding how applied public health practice would utilize what is learned in the classroom and preparing students for real-world application may be the missing link between theory and practice.